2007
DOI: 10.1016/j.chembiol.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Sterol 14α-Demethylase as a Potential Target for Antitrypanosomal Therapy: Enzyme Inhibition and Parasite Cell Growth

Abstract: Sterol 14alpha-demethylases (CYP51) serve as primary targets for antifungal drugs, and specific inhibition of CYP51s in protozoan parasites Trypanosoma brucei (TB) and Trypanosoma cruzi (TC) might provide an effective treatment strategy for human trypanosomiases. Primary inhibitor selection is based initially on the cytochrome P450 spectral response to ligand binding. Ligands that demonstrate strongest binding parameters were examined as inhibitors of reconstituted TB and TC CYP51 activity in vitro. Direct cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
194
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(203 citation statements)
references
References 51 publications
8
194
0
1
Order By: Relevance
“…Binding and Inhibition of TC14DM with Posaconazole, Fluconazole, and VNF-Although the apparent K d s determined by spectral titration are useful for primary identification of new binding ligands, they do not always correlate with inhibition of 14DM activity (12). Thus, we found that several imidazole derivatives that reveal nanomolar K d s were easily replaced in the enzyme reaction by substrate, whereas VNF derivatives were not (12).…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Binding and Inhibition of TC14DM with Posaconazole, Fluconazole, and VNF-Although the apparent K d s determined by spectral titration are useful for primary identification of new binding ligands, they do not always correlate with inhibition of 14DM activity (12). Thus, we found that several imidazole derivatives that reveal nanomolar K d s were easily replaced in the enzyme reaction by substrate, whereas VNF derivatives were not (12).…”
Section: Resultsmentioning
confidence: 78%
“…Thus, we found that several imidazole derivatives that reveal nanomolar K d s were easily replaced in the enzyme reaction by substrate, whereas VNF derivatives were not (12). On the other hand, some pyridine derivatives, which induce moderate spectral responses (the apparent K d s ϳ 0.2-0.5 M), turned out to be rather strong inhibitors of TC14DM (38).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations